Makalah Dinamika Islam di Brunei Darussalam - Mifta Yuljannah P; Zulkifli Nelson (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2024)
This study explores the dynamics of Islam in Brunei Darussalam, a country with a majority Muslim population that is rich in Islamic history and traditions. The main focus is on the evolution of the Islamic religion from the past to the present, as well as its impact on the social, political and economic life of Bruneian society. Various factors influencing the practice and understanding of Islam in the country are also discussed, including the role of government in managing religious affairs. This research uses a descriptive analytical approach by analyzing relevant literature and secondary sources to provide a comprehensive picture of how Islam plays a role in shaping national identity and regulating daily life in Brunei Darussalam.